Assessment of drug utilization pattern and risk factors for the development of diabetic neuropathy among type 2 diabetic patients in a south Indian hospital: A cross-sectional observational study - Lavanya Nalluri, Madhavi Mannam, Navya Vemireddy, Nandini Akula, Mounika Pothuraju, Dhanalakshmi Pinnika, Jaidev Sudagani, Ravindrababu Pingili, Naveen Babu Kilaru (Journal of Applied Pharmaceutical Science, 2019)
Diabetic peripheral neuropathy (DPN) is a well-known microvascular complication of type 2 diabetes mellitus (T2DM). DPN is defined as peripheral nerve dysfunction in diabetics after exclusion of other causes. To assess the prevalence of peripheral neuropathy in T2DM and the associated risk factors among in outpatients department in a south Indian hospital. A cross-sectional observational study was conducted on 868 subjects (509 with DPN and 359 without DPN). Prevalence of diabetic peripheral neuropathy was measured and risk factors for the development of diabetic peripheral neuropathy were determined by calculating odds ratios and drug utilization pattern was assessed. The prevalence of DPN in T2DM was significantly higher in the subjects who are married, uneducated, housewives, and urban residents. Many associated risk factors could affect T2DM leading to DPN such as hypertension, other diseases, endocrine diseases, history of cardiovascular diseases (CVD), >9 HbA1c, low high-density lipoproteins (HDL), high serum creatinine, long duration of diabetes, physical inactivity, and habit of taking junk foods (weekly once and weekly twice, soft drinks occasionally). The present study revealed that risk factors for the development of DPN were hypertension, endocrine diseases, history of CVD, poor glycemic control (>9 HbA1c), low HDL, high serum creatinine, long duration of diabetes, physical inactivity, habit of taking junk foods and soft drinks. Early detection of the identification of DPN in T2DM is needed in order to slow progression and complications. Metformin (40.47%), combination of glimepiride and metformin (29.93%), combination of human insulin and insulin isophane (22.7%) were mostly given to the T2DM patients with neuropathy.
Keywords: Diabetic neuropathy, prevalence, hyperglycemia, odds ratio.